2014
DOI: 10.2217/clp.13.82
|View full text |Cite
|
Sign up to set email alerts
|

Changes of prevalence of dyslipidemia among adults: a cross‑sectional study with a 2‑year follow‑up in urban southeast China

Abstract: Aim:To determine the prevalence of dyslipidemia in urban adults in southeast China. Patients & methods: A crosssectional survey was conducted by using a two-stage probability sampling design according to socioeconomic levels, sex and age in an urban representative sample of 11,877 Chinese adults aged 20-81 years in Shaoxing (Zhejiang, China) between 1998 and 2010. During 2011 and 2012, 11,620 subjects were thoroughly followed up with 93.5% in participation rate versus 99.0% in 2011 and 98.8% in 2012. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
4
12
0
Order By: Relevance
“…The prevalence of dyslipidemia in our study was partially comparable to figures reported in previous epidemiological studies [ 10 , 12 , 24 ]. For example, in a cross sectional study with a representative sample of 5,761 Chinese adults aged from 18 to 79 years, 35.40 % of the subjects had dyslipidemia [ 10 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The prevalence of dyslipidemia in our study was partially comparable to figures reported in previous epidemiological studies [ 10 , 12 , 24 ]. For example, in a cross sectional study with a representative sample of 5,761 Chinese adults aged from 18 to 79 years, 35.40 % of the subjects had dyslipidemia [ 10 ].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it may be the main contributor to the high TC in Shenzhen. Compared with studies carried out in some other regions, the prevalence of dyslipidemia components in Shenzhen were lower than those in Shanghai [ 24 ], Delhi [ 14 ], and Turkish [ 1 ], but a higher prevalence of high TC or high TG, and lower prevalence of high LDL-C or low HDL-C were found in Shenzhen than in Shaoxing [ 12 ]. The reported prevalence of dyslipidemia components varied among Shenzhen, Shanghai, Delhi, Turkish and Shaoxing, depending on the information available for the given population and the diagnostic criteria used.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Previous studies on dyslipidemia and associated factors have been conducted in different provinces and regions [5,[9][10] , but large-scale investigations in northern China are scarce. The Inner Mongolia Autonomous Region is located in the north of China and includes 12 cities.…”
mentioning
confidence: 99%